Physical and functional interaction between nucleoid‐associated proteins HU and Lsr2 of Mycobacterium tuberculosis: altered DNA binding and gene regulation. Issue 4 (11th February 2019) - Datta, Chandreyee; Jha, Rajiv Kumar; Ahmed, Wareed; Ganguly, Sohini; Ghosh, Soumitra; Nagaraja, Valakunja
Summary: Nucleoid‐associated proteins (NAPs) in bacteria contribute to key activities such as DNA compaction, chromosome organization and regulation of gene expression. HU and Lsr2 are two principal NAPs in Mycobacterium tuberculosis ( Mtb ). HU is essential for Mtb survival and is one of the most abundant NAPs. It differs from other eubacterial HU proteins in having a long, flexible lysine‐ and arginine‐rich carboxy‐terminal domain. Lsr2 of Mtb is the functional analogue of the bacterial NAP commonly called H‐NS. Lsr2 binds to and regulates expression of A/T‐rich portions of the otherwise G/C‐rich mycobacterial chromosome. Here, we demonstrate that HU and Lsr2 interact to form a complex. The interaction occurs primarily through the flexible carboxy‐terminal domain of HU and the acidic amino‐terminal domain of Lsr2. The resulting complex, upon binding to DNA, forms thick nucleoprotein rods, in contrast to the DNA bridging seen with Lsr2 and the DNA compaction seen with HU. Furthermore, transcription assays indicate that the HU‐Lsr2 complex is a regulator of gene expression. This physical and functional interaction between two NAPs, which has not been reported previously, is likely to be important for DNA organization and gene expression in Mtb and perhaps other bacterial species. Abstract : HU and Lsr2, two nucleoid‐associated proteins of Mycobacterium tuberculosis form a complex having DNA architectural and regulatory pattern distinct from their individual properties. Long, basic tail of HU interacts with acidic N‐terminal domain of Lsr2 to impart a new DNA‐binding mode.